The evidence base of US Food and Drug Administration approvals of novel cancer therapies from 2000 to 2020. Issue 12 (24th February 2023) - Gloy, Viktoria; Schmitt, Andreas M.; Düblin, Pascal; Hirt, Julian; Axfors, Cathrin; Kuk, Hanna; Pereira, Tiago V.; Locher, Clara; Caquelin, Laura; Walter‐Claudi, Martin; Lythgoe, Mark P.; Herbrand, Amanda; et al.
Abstract: Concerns have been raised that regulatory programs to accelerate approval of cancer drugs in cancer may increase uncertainty about benefits and harms for survival and quality of life (QoL). We analyzed all pivotal clinical trials and all non‐pivotal randomized controlled trials (RCTs) for all cancer drugs approved for the first time by the FDA between 2000 and 2020. We report regulatory and trial characteristics. Effects on overall survival (OS), progression‐free survival and tumor response were summarized in meta‐analyses. Effects on QoL were qualitatively summarized. Between 2000 and 2020, the FDA approved 145 novel cancer drugs for 156 indications based on 190 clinical trials. Half of indications (49%) were approved without RCT evidence; 82% had a single clinical trial only. OS was primary endpoint in 14% of trials and QoL data were available from 25%. The median OS benefit was 2.55 months (IQR, 1.33‐4.28) with a mean hazard ratio for OS of 0.75 (95%CI, 0.72‐0.79, I 2  = 42). Improvement for QoL was reported for 7 (4%) of 156 indications. Over time, priority review was used increasingly and the mean number of trials per indication decreased from 1.45 to 1.12. More trials reported results on QoL (19% in 2000‐2005; 41% in 2016‐2020). For 21 years, novel cancer drugs have typically been approved based on one single, often uncontrolled, clinical trial, measuring surrogate endpoints. This leaves cancer patients without solid evidence that novel drugs improve their survival or QoL and there is no indication towards improvement. Abstract : What's new? Concerns have been raised that regulatory programs to accelerate the approval of cancer drugs may increase uncertainty about survival and quality‐of‐life benefits and harms. Here, the authors analyzed all pivotal clinical trials and non‐pivotal randomized controlled trials for the 145 novel cancer drugs approved by the FDA between 2000 and 2020. Cancer drugs were typically approved based on one single small trial, often without a control group and measuring only surrogate endpoints. This leaves cancer patients without solid evidence that the novel drugs improve their survival or quality of life, with no trend towards change.